Viral distribution on asymptomatic onion (Allium cepa L.) plants - Velásquez-Valle, Rodolfo; Reveles-Hernández, Manuel; Amador-Ramírez, Mario Domingo (Revista Mexicana de Ciencias Agrícolas, 2018)
Using the DAS-ELISA method, the distribution of Onion yellow dwarf virus (OYDV), Garlic common latent virus (GarCLV), Shallot latent virus (SLV), Leek yellow stripe virus (LYSV), Tobacco etch virus (TEV) and tomato spotted wilt virus (TSWV) in the leaves, psdeudo-stem and the inflorescence of symptomless onion plants collected at dif ferent times in 2010, was studied in three locations in the State of Zacatecas, Mexico. We recorded the presence of these viruses in the organs just mentioned, although it was frequently detected mixed infections in single leaves where the most common interactions involved two, three or four viruses. There was no trend relating the viral presence with the analyzed vegetal organs or the leaf age; however, infections with only one virus appear to be less common in middle-aged leaves.
Keywords: incidence; mixed infections; onion; virus